Borges anacrônico, um escritor do século XIX no XX: diálogos com Domingo Faustino Sarmiento a partir da figura dos gauchos - Ian Anderson Maximiano Costa (2022)
The objective of this work is to study the anachronism in Borges's work through from the relationship that the writer establishes with Domingos Faustino Sarmiento and the figure of the gauchos in the nineteenth century. Those appear mainly in the River Plate literary genre known as gauchesca, having as one of its main representatives the Martín Fierro of Jose Hernandez. For a long time, Borgesian poetics would place in relation both the Facundo by Sarmiento and the Martín Fierro by José Hernández, both models canonical of Argentine literature would be incorporated by the writer conjugating civilization and barbarism. However, from the 1940s that synthesis began to change, Borges becomes even more involved in politics, becomes an "anti-Peronist", goes on to propose a opposition between civilization against barbarism, uses the nineteenth century in the figure of Sarmiento and Facundo to intervene in the 20th century. To achieve this route, the chosen corpus is made up of stories, essays and poems that teach how the 19th century cuts the entire work, from the years 1920-1930 of nationalist criollismo to the years of conservatism, namely: the stories are "Hombre de la Esquina Rosada" from the book Historia Universal de la Infamia (1935), “El Sur” from the book Ficciones (1944), the story “La Otra muerte” from the book El Aleph (1949) and the stories from El informe de Brodie (1970): “La intrusa”, "El indigno", "Historia de Rosendo Juárez", "El encuentro", "Juan Muraña", "El otro duelo".The prologues are: “El gaucho” (1968), “Domingo F. Sarmiento: Facundo” (1974), “Domingo F. Sarmiento: Recuerdos de provincia” (1944, 1974). And the poems: “Sarmiento” from the book El otro, el mismo (1964), “Los gauchos” from the book Elogio de la Sombra (1969) and “El gaucho” from book El oro de los tigres (1972). And even Sarmiento's own Facundo (1845).